Assessing the Significance of Hyperthermia in Newborns Undergoing Phototherapy for Hyperbilirubinemia - Trivedi, Krishna; D.-Williams, Janet; Rao, Rohan; Rometo, Allison; Miller, Benjamin (American Journal of Perinatology Reports, 2025)
About 2% of full-term neonates are evaluated for fever, with serious bacterial infections (SBIs) identified in roughly 10% of cases. The 2021 American Academy of Pediatrics guideline standardizes febrile neonate evaluation, but factors like phototherapy for hyperbilirubinemia can complicate decisions. Phototherapy-associated hyperthermia raises concern about distinguishing environmental causes from true infection. This study assessed the prevalence of hyperthermia in neonates receiving phototherapy and its association with SBI.We performed a retrospective chart review of neonates admitted for phototherapy at a quaternary pediatric hospital (2019–2022). Using International Classification of Diseases codes, we identified patients with hyperthermia (≥38°C) and reviewed whether they underwent SBI evaluation and follow-up within 2 weeks.Among 639 neonates, 9 (1.4%) developed hyperthermia. Two (22%) were diagnosed with an SBI; one had a negative SBI workup, and six were not further evaluated. None of the seven without SBI returned for care. The 1.4% hyperthermia rate is not higher than the general neonatal fever prevalence (2%).Hyperthermia during phototherapy is uncommon, but the 22% SBI rate in febrile neonates is noteworthy. Elevated temperatures in this context should not be presumed to be environmental. Clinicians should maintain vigilance and consider full SBI evaluations.
Keywords: neonate; fever; phototherapy; hyperbilirubinemia; serious bacterial infection; hyperthermia evaluation